2019
DOI: 10.15407/ubj91.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotic composition on oxidative/antioxidant balance in blood of rats under experimental osteoarthriti

Abstract: Osteoarthritis (OA) is a widespread pathology of the musculoskeletal system. OA may associate with a wide range of disorders, that lead to the development of various strategies on how to prevent and treat the disease. recent studies discussed interactions between the microbiome and a wide range of pathologies, including OA. In this study, we investigated the effect of probiotic cultures on oxidative/antioxidant balance in blood of rats during OA. Experimental OA was induced by a single injection of sodium mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Korotkyi et al [ 59 ] demonstrated that MIA-OA induced free radical reactions that caused the accumulation of superoxide anion radicals, hydrogen peroxide, and NO and thiobarbituric acid-reactive compounds that are intermediate products of lipid peroxidation. Elevated oxidative stress and ROS levels triggered by MIA led to the activation of the intrinsic pathway through the depolarization of membrane potential, the promotion of the discharge of cytochrome c, and the activation of caspase-3 [ 10 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Korotkyi et al [ 59 ] demonstrated that MIA-OA induced free radical reactions that caused the accumulation of superoxide anion radicals, hydrogen peroxide, and NO and thiobarbituric acid-reactive compounds that are intermediate products of lipid peroxidation. Elevated oxidative stress and ROS levels triggered by MIA led to the activation of the intrinsic pathway through the depolarization of membrane potential, the promotion of the discharge of cytochrome c, and the activation of caspase-3 [ 10 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-3 contributes to the overall apoptotic process by cleaving various cellular substrates [ 62 ]. Korotkyi et al [ 59 ] also mentioned that MIA-induced OA led to a decrease in superoxide dismutase (SOD) activity of glutathione (GSH) which represents the first line of antioxidants that catalytically scavenge the free radicals [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotic (PB) groups were administered an oral solution of "Multiprobiotic Simbiter®" (Company "О.D.Prolisok", Ukraine) -a biomass of living cells from the symbiosis of 17 strains of microorganisms physiological for mammalian intestines belonging to 11 species. Most strains were taken from All- The choice of this probiotic is due to its effective multicomponent live bacteria composition and previously shown by us anti-inflammatory and antioxidant properties for this pathology [10,11].…”
Section: Materials and Methods Animals And Treatmentsmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) affect the metabolism of extracellular matrix components and concerned as markers of joint tissue destruction [13,14]. In our previous studies, we found the effect of multistrain PB on the system disruption of free radical processes and levels of MMPs in the bloodstream during experimental OA [15,16], however, the local biochemical mechanisms of these processes were not shown in the cartilage yet. Therefore, the aim of this study to investigate the effect of a multistrain live probiotic on the oxidative-antioxidant balance and activity of MMPs in the cartilage of rats under conditions of experimental osteoarthritis.…”
mentioning
confidence: 99%